2013
DOI: 10.1039/c3cc46914j
|View full text |Cite
|
Sign up to set email alerts
|

Tandem regio- and diastereo-selective synthesis of halogenated C-vinyl glycosides from unactivated arylacetylenes

Abstract: A highly regio- and diastereo-selective synthesis of halogenated C-vinyl glycosides has been achieved from glycals and unactivated aryl acetylenes in the presence of halogenated Lewis acids via a tandem glycosylation-halogenation reaction. The Lewis acid used served the dual purpose of activating the allylic acetoxy group of glycals and serving as halogen source for Markovnikov addition across the triple bond, which makes the process atom economic. The synthesized glycosyl vinyl halides have been used as precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…Having established the optimal procedure for aryl- C -glycoside synthesis, we examined the cross-couplings between glycosyl halides and alkenylzinc reagents because vinyl C -glycosides are also potentially useful intermediates leading to a variety of carbasugars and C -glycosyl compounds . Among them, intra- and intermolecular glycosyl radical additions to alkynes are useful, because of their mild reaction conditions, which allow for the presence of various polar functional groups on the sugar derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Having established the optimal procedure for aryl- C -glycoside synthesis, we examined the cross-couplings between glycosyl halides and alkenylzinc reagents because vinyl C -glycosides are also potentially useful intermediates leading to a variety of carbasugars and C -glycosyl compounds . Among them, intra- and intermolecular glycosyl radical additions to alkynes are useful, because of their mild reaction conditions, which allow for the presence of various polar functional groups on the sugar derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Our reaction strategy was conceptualized on the basis of two of our reported works: one was the copper‐mediated synthesis of C‐alkynyl glycosides from unactivated acetylenes9a and the other was the preparation of halogenated vinyl C ‐glycosides from aryl acetylenes9b (Scheme ). In the former, we observed that there was in situ generation of triflic acid (TfOH), which expedited the reaction course unexpectedly.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, domino strategies for which new chiral centers with high functional diversity were generated, maintaining atom economy, have assumed great importance in synthetic chemistry. With our incessant curiosity in the development of new domino processes in carbohydrate chemistry,8,9b herein we report a domino, atom‐economic synthetic strategy for the generation of novel α,β,γ,δ‐conjugated diastereoselectively pure ( E , E )‐chalcone derivatives from glycals.…”
Section: Introductionmentioning
confidence: 99%
“…1 Dentre essas moléculas destacam-se os glicais. 2 Sabe-se também que os glicais são carboidratos largamente utilizados na síntese de O-glicosídeos, [3][4][5][6][7][8][9][10] C-glicosídeos, [11][12][13][14][15][16][17][18] S-glicosídeo, [19][20][21][22][23][24][25][26] e N-glicosídeos [27][28][29][30][31] (Figura 1); e vários tipos de oligossacarídeos. 32 Os mesmos servem como blocos de construção essenciais para síntese de 2-desoxi-hexoses e 2-desoxi-2-amino-hexoses e para síntese de produtos naturais oticamente ativos.…”
Section: Introductionunclassified